Three Principles for Market-Based Credit Regulation - Mehrling, Perry (American Economic Review, 2012)
A key lesson of the financial crisis 2007-09 is that the Bagehot Rule, “lend freely but at a high rate,” needs to be updated for the emerging market-based credit system. A modern rule is suggested: Markets, not Banks; Outside spread, not Inside spread; Core, not Periphery.